Intensitas Pemangkasan dan Pemupukan Tanaman Kopi Arabika yang Dilakukan oleh Petani di Desa Tebes Lues sebagai Upaya Peningkatan Produksi - Eliyin Eliyin; Syukri Mahara; Zulida Susanti; Ira Zulfa (Mikroba : Jurnal Ilmu Tanaman, Sains Dan Teknologi Pertanian, 2025)
Tebes Lues Village, located in a mountainous area, holds great potential as a production center for high-quality Arabica coffee. Coffee products from this village have been recognized in various local and international markets, known for their distinctive aroma and unique taste. Nevertheless, the productivity and quality of coffee in Tebes Lues Village can still be improved through the improvement of more modern and targeted cultivation techniques, one of which is through the application of proper pruning and fertilization techniques. This study aims to look at the types of pruning and fertilization carried out in Tebes Lues village as an effort to increase Arabica coffee production. The research was conducted with descriptive method by making a questionnaire containing interview questions to get info from respondents (farmers) related. The results of this study obtained that the type of pruning done by tebes lues village farmers is production pruning and branch pruning (Bayonet) and treatment of roots by doing mechanical processing. Fertilizers used by farmers in an organic way are SS, Phoska, ZA and Urea while organic fertilizers used are coffee skin, livestock manure, coffee skin pulp. Coffee production increased for farmers who pruned and fertilized intensively and periodically.